Understanding Engineering Identity Experiences for Asian American Women in Higher Education - Maria L. Espino; Michelle C. Ausman; Brian D. Le; Sarah L. Rodriguez; Katie Koo (Studies in Engineering Education)
Background: Research has demonstrated the importance of engineering identity as a precursor to persistence within engineering education. Asian American women (AAW) college students possess unique engineering identity experiences during college, yet little research to date has focused on their educational journeys. Purpose/Hypothesis: This qualitative, phenomenological research study explored how Asian American women college students developed and maintained engineering identities. Design/Method: The study uses a phenomenological approach to explore the lived experiences of seven Asian American women college students. Interviews sought to derive the essences of how Asian American women (AAW) college students understood their engineering identities, including how they became interested in engineering, gained (or did not gain) recognition as an engineering person from others, and performed their engineering identities. Students participated in two to four interviews, depending on their time within the larger longitudinal project, funded by the National Science Foundation (NSF). Results: The study found that intersectionality was a key element for the engineering identity experiences of AAW. In addition, the ability to bring one’s whole self to engineering was influential in feeling more like an engineer. Finally, this study also demonstrated a range of identity experiences across the AAW subgroup. Conclusions: The findings demonstrate the need for AAW students to be able to bring their whole selves to engineering settings and highlight the importance of intersectionality for engineering identity experiences.